Exploring the Role of BIM In Supporting Sustainable Design and Construction of Green Buildings - Iqbal, Hafiz Muhammad Afzal; Chaudhry, Imran Ghafoor; Cheema, Shahan Mehmood (Annals of Human and Social Sciences, 2024)
Sustainable design and construction have amassed outstanding recognition in the construction of green buildings, resulting in revolutionary improvements to authenticate these aspirations. Building information modeling (BIM) achieving momentum as a potent software for enhancing sustainability in construction. This research explores BIM’s input to support sustainable design and construction in green buildings, trying to analyze its acknowledgment, improvement, and benefits among professionals. It explores BIM's implication on sustainable design principles, cooperation, and project efficacy, and emphasizes factors like energy effectiveness, selection of material, sustainable indoor air quality, and resource streamlining. Through a mixed-method strategy, this research emphasizes BIM's assurance to enhance sustainable design principles and improve project delivery. Findings share insight and guidance for practitioners and participators, supporting wider BIM collaboration to achieve sustainable construction targets competently. Integration of BIM’s software with laboratory concrete tests to achieve high-quality construction and continuous monitoring of the project.